INTERNATIONAL STRATEGIES FOR COUNTERING CYBER THREATS AND PROTECTING THE GLOBAL ECONOMY; A CASE STUDY OF CHINA AND FRANCE - Ali Mahmood Salman (Tikrit Journal For Political Science, 2026)
Cybersecurity has become a pressing global issue that has implications for national security, international relations, and economic stability worldwide. In an effort to study how governments develop and implement strategies to thwart cyberattacks and protect critical infrastructures this research offers a comparison of China and France. The analysis presents several key dimensions of governance including: legal frameworks, risk management, safety culture, technology sovereignty, incident response, and international cooperation, among others. The findings indicate two dissimilar frameworks. France practices a multi-level cooperative strategy that blends national initiatives with European policies and transatlantic collaborations, while China adopts a state-centric and sovereignty-driven approach that emphasizes regulation, technological independence, and centralized governance. The study emphasizes critical divergences in international alignment, transparency, and inclusivity, and elaborates on how these approaches shape international cooperation and domestic resilience. The paper contributes to political science conversations on cybersecurity governance by providing lessons from both cases as case studies. It also provides policy recommendations for creating models that strike a balance between protecting national sovereignty and boosting global security.